Improving the Creative Economy of the Community Through Training and Processing the Local Potential of Candlenut and Utilizing Digitalization as A Marketing Medium in Emburia Village, Ende Sub-District - Jamu, Maria Endang; Langga, Lambertus; Sari, Santy Permata; Byre, Rafael Octavianus (Unram Journal of Community Service, 2024)
Local potential is the natural, cultural, and natural resources of a region.  Emburia Village, Ende Sub-District, Ende Regency is one of the villages that is the largest producer of candlenuts in Ende Regency, but this large candlenut potential has not been maximally utilized for the economic income of the community. The candlenuts produced are only sold to traders in Ende city. Therefore, this community service activity is deemed important to be carried out in Emburia village with the target participants being PKK (Family Welfare Empowerment) women. Community service activities go through several stages including the preparation stage, preparation and implementation stage until the finished product with the brand name MIKERIA (Emburia hazelnut oil). This activity is expected to provide understanding to participants in improving the creative economy through training and utilization of digital marketing in marketing products, namely hazelnut oil